Pembelajaran Kosakata Bahasa Arab yang Menarik dengan Media Pembelajaran Bergambar - Vira Arbangka; Muh Arif; Abdullah; Yuslin Kasan (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2023)
The purpose of this study is to describe the effectiveness of using picture media to enhance vocabulary acquisition. The type of research used in this study is descriptive qualitative. The researcher employed several data collection techniques, including observation, interviews, and documentation. The data analysis techniques include data reduction, data presentation, and verification. The results of this study indicate that: (1) The Arabic language learning process at MTs Negeri 3 Gorontalo Regency, using picture cards, runs smoothly. The use of picture cards can only be conducted in person and not through online learning. (2) The use of picture cards at MTs Negeri 3 Gorontalo Regency can improve students' vocabulary acquisition, as indicated by the statements of subject teachers who have used picture cards in the learning process.